Pediatric pituitary resection: characterizing surgical approaches and complications. Issue 1 (14th September 2016) - Hanba, Curtis; Svider, Peter F.; Shkoukani, Mahdi A.; Sheyn, Anthony; Jacob, Jeffrey T.; Eloy, Jean Anderson; Folbe, Adam J.
Abstract : Background: Although there has been extensive study evaluating adult pituitary surgery, there has been scant analysis among children. Our objective was to evaluate a population‐based resource to characterize nationwide trends in surgical approach, hospital stay, and complications among children undergoing pituitary surgery. Methods: The Kids' Inpatient‐Database (KID) files (2009/2012) were evaluated for pituitary gland excisions. Procedure, patient demographics, length of inpatient stay, inpatient costs, hospital setting, and surgical complications were analyzed. Results: A weighted incidence of 1071 cases were analyzed; the majority (77.6%) underwent transsphenoidal resections. These patients had significantly decreased hospital costs and lengths of stay. Patients undergoing transfrontal approaches had significantly greater rates of postoperative diabetes insipidus (DI) (66.5%), panhypopituitarism (38.8%), hydrocephalus, and visual deficits. Among transsphenoidal patients, males had greater rates of postoperative hydrocephalus (5.5%) and panhypopituitarism (17.5%) than females, and patients ≤10 years old had greater rates of these 2 complications (14.5%, 19.4%, respectively) as well as DI (61.3%). Conclusion: A greater proportion of children undergo transfrontal approaches for pituitary lesions than in their adult counterparts. This difference may harbor a potential to influence future sellar resection approaches in children toward a transsphenoidal operation when surgically feasible. Patients undergoing transfrontal procedures have greater risks for many intraoperative and postoperative complications relative to individuals undergoing transsphenoidal resections. Among patients undergoing transsphenoidal approaches, males had significantly greater rates of postoperative hydrocephalus and panhypopituitarism, and younger children had greater rates of postoperative DI, hydrocephalus, and panhypopituitarism. These data reinforce the need for greater vigilance in the postoperative care of younger children undergoing transsphenoidal surgery.